Digitising the on-call medical team's patient list system: a QIP - Fahad-Bin Zahid (Future Healthcare Journal, 2025)
Introduction: At New Cross Hospital, the on-call medical team historically relied on a paper-based referral system. This posed challenges, including frequent loss of sensitive patient information, inefficient handovers and no audit trail. Recognising these issues, I independently developed a SharePoint-integrated Excel system to address these problems. Materials and methods: Baseline issues with paper-based system (survey results): • 66.7% of registrars dissatisfied or very dissatisfied with the paper system; • 80% reported issues such as lost lists or incomplete information; • 41% of registrars reported incidents of losing paper lists; • 86.7% of respondents reported finding the handover process time-consuming or error-prone; • Average time spent rewriting patient details during handovers: 10–30 min. • Key metrics monitored: • Reduction in handover times; • System usability (user interaction with features, such as priority setting, location etc); • Feedback on efficiency and user satisfaction; • Environmental impact: complete elimination of paper lists.Framework used: plan–do–study–act (PDSA)System development: • A live Excel-based patient list hosted on SharePoint and accessible MS Teams channel; • Features: priority setting, timestamping, real-time logging, clerking status updates, specialty columns, and live accessibility for all members within the designated MS teams channel.Stakeholder engagement: • Regular feedback sessions with registrars and consultants; • Collaboration with the digital innovation team.Sustainability principles: • Eliminated paper waste, thus reducing the environmental impact and securely archiving older lists within a Trust-approved system for auditability and governance; • Used existing infrastructure for minimal financial investment. Results and discussions: The system was piloted during night shifts and expanded across five improvement cycles (each month was considered a cycle). Feedback was collected after each cycle to address challenges and refine functionality, including: • Removal of unnecessary columns • Removal of the ‘low-priority’ category (eg, falls, social issues), because such patients were delayed for extended periods, raising clinical safety concerns; • Improved navigation by fixing headers and introducing alternate row colouring to support dyslexic users1–3; • Enhanced visibility for same-day emergency care department (SDEC) and patients who were post-take; • Created a video guide for staff and clarified the log-in process; • Created a secure folder for archived spreadsheets to improve data storage; • Developed an automatic timestamp for when details were entered.Efficiency gains: • Reduced handover times by 13.5 min (on average) per handover; • 73% of registrars reported improved workflow efficiency; • Features, such as live updates and centralised tracking, minimised information loss and streamlined referral management.Environmental impact: • Eliminated 100% of official paper-based referral list, aligning with NHS sustainability goalsUser satisfaction: • 91% of registrars preferred the electronic system. • 73% rated the system 8–10 for usabilityEquality impact: • The project had no adverse effects on any protected characteristic groups. Instead, it demonstrated positive impacts. • Disability: the use of alternate row colouring in the spreadsheet significantly supported registrars with dyslexia.So far, I have demonstrated significant improvements in workflow efficiency, patient safety and environmental sustainability. By eliminating paper waste, reducing manual processes and ensuring high user satisfaction, this QIP successfully transitioned the on-call medical team from a paper-based to an electronic system, achieving 100% utilisation for referrals. I also developed a SOP for Governance.Moving forward, the focus will be on refining the system further based on feedback.